Utilization of Benenai River Water for Household Needs in Nunfutu Village, Fatukopa District, South Central Timor Regency - Ride Benu; Muhammad Husain Hasan; Ahmado Hamado (Tinta Emas Institute, 2025)
This study aims to describe how the people of Nunfutu Village use the water from the Benenai River, identify the factors that encourage the community to use the Benenai River as their main water source, analyze the impact of using the Benenai River water on the community's health and daily life, and find out how the community perceives the quality of the Benenai River water. This research was conducted from June 26 to July 21, 2025, in Nunfutu Village. This research was conducted using survey and interview methods with a qualitative approach consisting of several data collection techniques, namely observation, interviews, and documentation. The number of respondents was 30 people. The data analysis used in this study was qualitative descriptive analysis. Data processing included data reduction, data presentation, and conclusions or verification. The results of this study show that the uses of water from the Benenai River in Nunfutu Village include cooking, washing, bathing, drinking, and defecating. The factors driving the use of water from the Benenai River include limited availability of clean water, necessity, economic factors, awareness and education, cultural factors, and extreme natural conditions. The impact of using water from the Benenai River on the community includes positive and negative effects on health, time, and energy. The perception of the Nunfutu Village community regarding the quality of water from the Benenai River is still very low.